Epidemiological and Clinical Features of Diaper Dermatitis in Infants at the Yaounde Gynaeco-Obstetric and Pediatric Hospital, Cameroon - Chiabi, Andreas; Ngamgo Kamdem, Jenny Christelle; Nkoro, Anita Grâce; Siyou, Hippolyte; Mah, Evelyn; Nguefack, Félicitée Dongmo; Nguefack, Seraphin; Angwafo, Fru, III (Journal of Child Science, 2018)
Diaper dermatitis is defined as an inflammatory reaction localized on the skin that is usually covered by the diaper (genitals, buttocks, and anus). The aim of this study was to determine the prevalence of diaper dermatitis and to describe the clinical presentation and practices related to hygiene in infants with diaper rash at the Yaounde Gynaeco-Obstetric and Pediatric hospital. It was a descriptive cross-sectional study undertaken in 1,004 mother–children pairs. Data were collected using structured questionnaires during face-to-face interviews with the parents. The prevalence of diaper dermatitis was 18.4%, and infants were aged 7 days to 24 months with a mean age of 5.91 months. The most represented age group was 0 to 6 months (67.6%). Infants living in urban areas (59.5%), of unemployed mothers or guardians (30.3%), and those of mothers living as a couple (75.1%) were most represented in our study sample. The majority of infants used both disposable and reusable diapers (48.6%). In addition, 72.7% mothers used palm kernel oil, and 27.3% rubbed other ointments before changing the baby's diapers. The most frequent clinical form was the chaffing form (48.1%). Healthcare personnel should inform, educate, and communicate with mothers on body hygiene of their babies to avoid this disorder, which can cause severe discomfort and sometimes lead to complications.
Keywords: diaper rash; infant; epidemiology; clinical features